Research in organizational change and development. Vol. 27 - Shani, Abraham B. Rami; Noumair, Debra A. (Research in organizational change and development, 2019)
Volume 27 of Research in Organizational Change and Development introduces thought-provoking insights on inclusivity within organizations. These include: the philosophical foundation of organization development and change; positive organizational scholarship as a scientific base for sustainable change; the practice of humility and humble behaviors; a socio-economic approach to organization development enhancing the compatibility between the human system, stakeholders, and stockholders; the importance of collaborative effort across hierarchies and vertical boundaries, despite tensions that undermine middle managers' role as change agent; the use of top-down and bottom-up processes to link attitudes and enhance levels of engagement; how leaders in social enterprise development continuously respond to common paradoxes of engagement; and, finally, enhancing a culture of inclusive, agile and thriving teams in environments of continuous change. The diverse collaborative contributions by leading scholars and scholar-practitioners from across the globe provide an enriching body of knowledge on contemporary challenges in organizational change and development.